(untitled) (Homoeopathy for All, 2025)
The most prevalent illness in children between the ages of two to fifteen is tonsillitis. Recurrent tonsillitis can result from multiple acute attacks of the disease each year or from an acute attack that occurs just once a year. In children, this may result in more serious issues. When treating both acute and recurrent episodes of tonsillitis, homoeopathic treatment works better. Three essential requirements for a The most prevalent illness in children between the ages of two to fifteen is tonsillitis. Recurrent tonsillitis can result from multiple acute attacks of the disease each year or from an acute attack that occurs just once a year. In children, this may result in more serious issues. When treating both acute and recurrent episodes of tonsillitis, homoeopathic treatment works better. Three essential requirements for a homoeopath are remedy, potency, and dose to treat the acute state of tonsillitis and manage repeated bouts. are remedy, potency, and dose to treat the acute state of tonsillitis and manage repeated bouts.